2021
DOI: 10.1001/jamanetworkopen.2021.24124
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Women and Reporting of Outcomes by Sex in Clinical Trials for Alzheimer Disease

Abstract: IMPORTANCE Women represent two-thirds of patients with Alzheimer disease (AD), and sex differences might affect results of randomized clinical trials (RCTs). However, little information exists on differences in sex as reported in RCTs for AD.OBJECTIVE To assess the ratio of females to males and the reporting of sex-stratified data in large pharmaceutical RCTs for AD.DATA SOURCES A search for pharmaceutical RCTs for AD was conducted on September 4, 2019, using ClinicalTrials.gov with the key word Alzheimer dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 110 publications
(471 reference statements)
3
25
0
1
Order By: Relevance
“…Indeed, the number of publications on sex differences in diseases has substantially increased in the last decade (trends data from PubMed). Similar increasing temporal trends were observed in two recent analyses of reporting of results by sex in clinical trials of acute stroke therapies and Alzheimer's disease 13,22 . However, the reporting of outcomes by sex is still largely suboptimal as only 40% of RCTs of AF published in 2020 and 2021 reported sex‐specific outcomes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, the number of publications on sex differences in diseases has substantially increased in the last decade (trends data from PubMed). Similar increasing temporal trends were observed in two recent analyses of reporting of results by sex in clinical trials of acute stroke therapies and Alzheimer's disease 13,22 . However, the reporting of outcomes by sex is still largely suboptimal as only 40% of RCTs of AF published in 2020 and 2021 reported sex‐specific outcomes.…”
Section: Discussionsupporting
confidence: 68%
“…Similar increasing temporal trends were observed in two recent analyses of reporting of results by sex in clinical trials of acute stroke therapies and Alzheimer's disease. 13,22 However, the reporting of outcomes by sex is still largely suboptimal as only 40% of RCTs of AF published in 2020 and 2021 reported sex-specific outcomes. We observe higher rates of reporting in NEJM (87.5%) and Lancet (50.0%), in keeping with a 2016 review on sex-related reporting in RCTs in the NEJM and Lancet journals in which 48% of trials reported results by sex, 15 and with a more recent review on trials of acute stroke therapies which showed 61% and 40% sex-specific reporting in trials published in the NEJM and Lancet, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-related differences in absorption and excretion, distribution and metabolism of drugs have been described and more adverse drug reactions have been reported in females compared with males ( Whitley and Lindsey, 2009 ) highlighting sexual dimorphic responses to drugs, notably drugs that affect the CNS. In the context of AD, a recent review and metanalysis reported that only 7 out of the 56 randomized clinical trials in AD included reported sex-stratified results and concluded ( Martinkova et al, 2021 ) and the relative lack of data on sex-related differences in drug efficacy has been noted ( Ferretti et al, 2018 ). In the light of this, a call has been made for specific analysis of gender effects on drug treatments in AD ( Schwartz and Weintraub, 2021 ) but this cannot be confined to AD and the principle should apply broadly, but particularly in conditions where clear sex-related differences in disease incidence exists.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, clinical trials of drugs for treatment of AD have a very high degree of failure, suggesting that individual factors should be taken into account both in searching new treatments and in designing clinical trials [42]. Biological sex is one such factor; a recent meta-analysis showed that the proportion of women enrolled in clinical trials for AD is lower than in the general AD population, and that it correlates with severity of symptoms in the enrolled population [43]. An appraisal of the impact of sex on cognitive decline and treatment response in Alzheimer is pivotal to build personalized treatment tailored to the unmet clinical needs of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research supports the need to account for sex in investigating prospective treatments for AD [43] This should be integrated with the most powerful recent developments in digital medicine to build models of disease development that can fully integrate the effect of sex, digital biomarker technology being one of the most promising tools. The final objective is to build an integrated framework for sex-stratified prediction, monitoring and personalized treatment of neurodegenerative diseases, as supported for example by the Alzheimer's Precision Medicine Initiative [55].…”
Section: Discussionmentioning
confidence: 99%